Case reports: Legg-Calve-Perthes disease in Czech archaeological material - Smrčka, Václav; Mařík, I; Svenssonová, Markéta; Likovský, Jakub (Clinical orthopaedics and related research, 2009)
Legg-Calve-Perthes disease (osteochondrosis of the femoral head) has been recognized in archaeological material for nearly a century but is extremely rare. We describe two Czech cases from archaeological findings. The first case was diagnosed in the skeleton of a man older than 50 years with the left hip affected. The skeleton was in grave Number 2 of the Langobard cemetery at Luzice (Moravia) and dated to the end of the fifth century and the beginning of the sixth century AD. The second case was described by J. Chochol in 1957 on the left femur and half of the pelvis of a skeleton from an archaeological investigation in Brandysek (Bohemia), ninth to tenth centuries AD. Using the diagnostic criteria of Ortner and Putschar, we excluded slipped capital femoral epiphysis in both cases. We discuss the differential diagnosis of Legg-Calve-Perthes disease versus unilateral and bilateral osteochondroses of the femoral head in archaeological and current clinical material.
Keywords: Pelvis; Legg-Calve-Perthes Disease; Humans; lidé; hlavice femuru; History, Medieval; Archaeology; Czech Republic; dějiny středověku; Femur Head; pánev; Male; archeologie; mužské pohlaví; Perthesova nemoc; Česká republika; Hip Joint; Paleopathology; kyčelní kloub; paleopatologie